PAK ADI Based Small Ball Game Development Model to Improve Physical Learning In Elementary Schools - Yusnadi; Ramlan Mahmud (Jurnal Pendidikan Indonesia, 2026)
Elementary school students' small-ball game skills have not yet developed optimally because physical education instruction remains predominantly teacher-centered and has not adopted innovative learning models. This study aimed to analyze the effectiveness of the PAK ADI learning model (Participatory, Analytical, Creative, Active, Demonstrative, and Innovative) in improving elementary school students' small-ball game skills. This study employed a Research and Development (R&D) method based on the Borg and Gall model, consisting of the stages of preliminary research, planning, validation, evaluation and revision, and model implementation. The research participants included subject-matter experts, instructional experts, physical education teachers, and elementary school students involved in both small-group and large-group trials. Data were collected through classroom observations, validation questionnaires, user response questionnaires, and small-ball game skills tests. The research instruments consisted of expert validation sheets, observation sheets, practicality questionnaires, and learning outcome tests. Data were analyzed using descriptive qualitative and quantitative techniques, while the effectiveness of the model was evaluated using an independent t-test at a significance level of 0.05 with the assistance of the Statistical Package for the Social Sciences (SPSS). The findings indicated that the PAK ADI learning model met the criteria of validity, practicality, attractiveness, and effectiveness in improving elementary school students' small-ball game skills. Therefore, the PAK ADI learning model is suitable as an innovative alternative for physical education instruction to enhance both the quality of learning and students' small-ball game skills.